Genomic Divergence of Sympatric Lineages Within Stichopus cf. horrens (Echinodermata: Stichopodidae): Insights on Reproductive Isolation Inferred From SNP Markers - Kenneth M. Kim; Apollo Marco D. Lizano; Robert J. Toonen; Rachel Ravago‐Gotanco (Ecology and Evolution)
ABSTRACT How reproductive barriers arise in early stages of divergence among broadcast spawning organisms that exist in sympatry remains poorly understood. Reproductively isolated lineages (Clade A and B) of Stichopus cf. horrens were previously reported across the western Pacific, with an additional putative cryptic species detected within the Clade B lineage warranting further examination. The present study further examines the hypothesis that the two mitochondrial lineages (Clade A and Clade B) of Stichopus cf. horrens represent putative cryptic species and whether another cryptic species within the Clade B lineage exists using a reduced representation genomic approach. Using double‐digest RAD (ddRAD) sequencing, a total of 9788 single nucleotide polymorphism (SNP) markers were used to examine divergence among Stichopus cf. horrens lineages (n = 82). Individuals grouped into three SNP genotype clusters, broadly concordant with their mitochondrial lineages and microsatellite genotype clusters, with limited gene flow inferred among clusters. Outlier analysis recovered highly divergent SNP loci with significant homology to proteins related to rhodopsin and tachykinin receptor signaling, sperm motility, transmembrane transport, and hormone response. This study confirms the existence of three reproductively isolated genotype clusters within Stichopus cf. horrens and highlights gene regions related to reproduction that may contribute to establishing reproductive barriers between broadcast spawning species at an early stage of divergence.